JURIDICAL ANALYSIS OF THE ROLE OF ADVOCATES IN PROVIDING NON-LITIGATION LEGAL ASSISTANCE AS AN EFFORT TO RESOLVE DISPUTES OVER DOCTORS' MEDICAL ACTIONS IN HOSPITALS (CASE STUDY IN HOSPITALS) - Annisa Dea; Irsyam Risdawati; Redyanto Sidi (RADJA PUBLIKA, 2025)
The purpose of this study is the importance of the role of advocates as providers of non-litigation legal aid as an effort to resolvedisputes in the world of health, one of which is medical actions carried out by doctors in carrying out professional obligations thatresult in the risk of lawsuits. Therefore, in this condition, this study is directed to examine the role of advocates in providing legal aid to medical personnel based on Law Number 18 of 2003 concerning Advocates, and linking it with the new Law Number 17 of 2023concerning Health and Law 29 of 2004 concerning Medical Practice. For this reason, this study uses a qualitative descriptive method, namely research based on library research that reviews related laws and regulations. The results of the study indicate that advocates have an important role in providing non-litigation legal assistance to patients and medical personnel, such as providing legal consultations, helping to prepare documents, contacting hospitals, helping to gather information, mediating, providing advice, helping to process certificates and licenses, and helping to deal with complaints. It also shows that advocates have a strategic and important role in providing legal protection to medical personnel, where advocates must provide legal assistance services with fullresponsibility, integrity, and professionalism with the aim of realizing justice and recommending advocates to continue to develop special expertise in the health sector and deepen their knowledge of health regulations and regulations in order to achieve maximum legal assistance and can benefit all parties.